Computational hemodynamic investigation of a new bileaflet mechanical heart valve. (May 2020) - Khellaf, Belkhiri; Boussad, Boumeddane
In this paper, we perform a numerical analysis for simulating steady, two-dimensional, laminar blood flow through our proposed design, known as the Butterfly mechanical heart valve, where the leaflets are fully opened. Blood has been assumed to be Newtonian and non-Newtonian fluid using the Casson model for shear-thinning behavior. A non-uniform Cartesian grid generation technique is presented to generate a two-dimensional grid for the irregular geometry of the Butterfly valve. The governing Navier–Stokes equations of flow, written in a stream function–vorticity formulation, are solved by the finite difference method with hybrid differencing of the convective terms. The computed results show that the blood's non-Newtonian nature significantly affects the flow field with the existence of recirculation and consequently stagnation causing thrombus formation, as well as an increase of the shear stress along the wall, which contributes to hemolytic blood damage. The results demonstrate that the model is capable of predicting the hemodynamic features most interesting to physiologists. It can be used to assess thromboembolic problems occurring with heart valves and in the design of cardiac prostheses.